Design and Characterization of Resistance Sensor to Optimize the Manufacturing of Infuse Water Lemon and Sprite Water Lymon Detection System - Alfiah, Fia Ismi Nur; P, Dinda Salsabila; Rakhmadi, Frida Agung (Proceeding International Conference on Science and Engineering, 2020)
This research was purposed to design and characterize a resistance sensor. This research was conducted with three phases: designing, manufacturing and characterization of resistance sensor. Sensor design was done using the 3D paint software. The tools used in sensor manufacturing were PCB, resistors, and copper wire. The tools used in sensor characterization were power supply, ohmmeter and samples of infuse water lemon and sprite water lymon. Sensor characterization was done by varying samples of 50ml, 100ml, 150ml. Data acquisition for each of samples was repeated 3 times. The result of this research was showed an average and unpredictability with the repeatability resistance sensor on the sample of infuse water lemon (1,215 ± 0,723) V with repeatability 99.05% while for samples of sprite water lymon amounting to (1,12 ± 1,345) V with repeatability 99.24%. And was retrieved the value of the transfer function for sample infuse water lemon is y = (4,757-0.03542x) and for sample sprite water lymon is y = (1.40666-0.0028666x). This tool can be developed as a detection tool using resistance-based sensors.